Review of pilot plant scale approach on polluted river water treatment technology - Hamdan, Mohamad Alif Hakimi; Madon, Rais Hanizam; Mohammad Dzulkifli, Farzana Balqis; Hairom, Nur Hanis Hayati; Muhamad, Aida; Abdullah, Iqbal Shahridzuan; Maulad Sapuan, Azri Amnani (2024)
Over time, population increase, migration, urbanization, and industrialization have influenced freshwater demand throughout time. Scaling-up the water treatment from modest to large-scale is important in order to suit human demands. Therefore, this research attends to review the potential of a pilot plant-scale for the treatment of polluted river water. In recent years, there have been many studies into lab-scale for the polluted river water treatment. However, there is little discussion on the pilot-scale polluted river water treatment by the previous studies. Thus, this review goes into the depth studies on the polluted river water treatment in a large scale by previous literature